Rehabilitacja - od starożytności do współczesności = Rehabilitation from antiquity to modernity - Piotr Biegański; Emilia Polewska (Kazimierz Wielki University, 2015)
The first mention of rehabilitation dates back to the Chinese emperor Hoong - Ti - 3 thousand years BC. Forms used in later years as the treatment of light, heat, water or manual work are the cornerstones of today's manual body work carried out by physiotherapists. With the development of human knowledge about the body and functions increased until the rapid development of rehabilitation in the XX century through the creation of a structured system of education, research, the creation of treatment therapy.